2022
DOI: 10.1186/s13018-022-03133-1
|View full text |Cite
|
Sign up to set email alerts
|

A clinical and biomechanical comparison of INFIX plus single versus double sacroiliac screw fixation for unstable pelvic ring injury

Abstract: Background The aim of this study is to compare the clinical and biomechanical outcome of INFIX plus single with two sacroiliac screw fixation for unstable pelvic fractures of Type C. Methods Sixteen cadavers were randomly subjected to INFIX plus single or double sacroiliac screw fixations and then mounted onto the ElectroForce loading machine under different vertical loads. To investigate the clinical outcomes of the two techniques, nineteen patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In addition, the study revealed that compared to the canulated screw, the elastic nail exhibited significantly lower peak stress and a more dispersed stress distribution, suggesting better biocompatibility. Previous research has confirmed the biomechanical stability of INFIX for anterior pelvic ring injuries 23 , 28 , 29 . However, ESIN proved superior in stability compare to INFIX, both globally and locally.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, the study revealed that compared to the canulated screw, the elastic nail exhibited significantly lower peak stress and a more dispersed stress distribution, suggesting better biocompatibility. Previous research has confirmed the biomechanical stability of INFIX for anterior pelvic ring injuries 23 , 28 , 29 . However, ESIN proved superior in stability compare to INFIX, both globally and locally.…”
Section: Discussionmentioning
confidence: 61%
“…Studies have shown that the probability of implant failure is different when only the posterior ring fixation is used in the case of instability of the posterior and/or anterior ring instability. In elderly patients, the failure rate of single-screw fixation was 12% when the posterior ring was injured alone and can be as high as 55% when the anterior and posterior ring were unstable simultaneously 13 . In our study, wound discharge was found to be a common complication, mostly related to the liquefaction of fat at the wound site.…”
Section: Discussionmentioning
confidence: 99%
“…When axial loading reaches 400 N to 800 N, no difference in posterior pelvic ring stability between the single- and double-screw fixation techniques. However, if combined with anterior pelvic ring injury, significant differences will emerge 13 . Stabilizing both S1 and S2, preferably with trans-sacral screws, could probably reduce the re-operation rate 14 .…”
Section: Methodsmentioning
confidence: 99%
“…Most of the anterior pelvic rings are located subcutaneously and are easily damaged when subjected to external forces, resulting in a breakdown of the integrity and stability of the pelvis [2,3]. Currently, the mainstream treatment methods for anterior pelvic ring injuries include external xation, internal xation with incisional repositioned plates, and INFIX [4]. External pelvic xation frame is commonly used in patients with multiple trauma and hemodynamic instability, which can quickly stabilize and reduce the volume of the pelvic ring, reduce the "chimney effect" caused by pelvic ring rupture, and reduce bleeding [5].…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars believe that incision and plate xation of the anterior pelvic ring is the best treatment method because the fracture end can be repositioned under direct vision after incision, and the plate and screws can obtain good repositioning effect and biomechanical stability [4,9]. However, the disadvantages of large bleeding, vascular nerve injury, incisional infection, extensive periosteal debridement, and complicated surgical operation have seriously limited the further application of this technique [10].…”
Section: Introductionmentioning
confidence: 99%